Legal Protection of the Parties in Construction Agreements - Setiawan, Budi; Markoni (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2024)
Construction agreements in Indonesia are an important legal instrument that often faces challenges due to the complexity of regulations and the potential imbalance of power between parties. This study aims to analyze the legal framework governing construction agreements in Indonesia and identify the importance of dispute resolution in the context of construction projects. This research uses a literature study to analyze the legal framework governing construction agreements, including the Civil Code, Law Number 2 of 2017 on Construction Services and Government Regulation Number 17 of 2013. This analysis reveals the importance of dispute resolution, especially through arbitration, as an effective mechanism to address conflicts in construction projects. The role of legal consultants with expertise in construction law is also crucial in guiding stakeholders in drafting agreements that protect the interests of each party and minimize legal risks. This study emphasizes the need for careful attention to legal protection in construction agreements to ensure fairness and the success of the project.